Studi Kritis terhadap Corak dan Metode Penafsiran Tiga Mufassir Nusantara: Abd Al-Rauf As-Sinkili, Syaikh Nawawi Al-Bantani dan Kiai Sholeh Darat - Gunawan Hasibuan, Akmal Rizki; Hakim, Luqmanul; Rowiyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This paper aims to expound on the dynamics of Al-Qur'ān teaching in the archipelago. Since ancient times, the archipelago has not only had natural resources but also skilled human resources in various fields, especially the learning of Al-Qur'ān. In this article, the author uses a descriptive method with the aim of describing three Indonesian ulama and their methods and styles of interpretation systematically by referring to academic sources. This article finds that there is criticism from orientalists and commentators on Indonesian scholars who say that Tarjuman Al-Mustafid's commentary is a translation of Jalalain's commentary or Imam Baidhawi's commentary. This is not appropriate in the author's opinion after reviewing several sources. Apart from that, this article also contains differences of opinion from commentators regarding the styles used by three Indonesian commentators which will be analyzed by the writer. Thus, the three early Indonesian scholars who will be discussed by the author are ‘Abd Al-Rauf As-Sinkili with his tafsir book Tarjumān Al-Mustafῑd complete with 30 juz, which was discovered in the 17th century. This tafsir uses Malay-Jawi. Then, Imam Muhammad Nawawi Al-Bantani with his commentary, namely Tafsῑr al-Munῑr Li Ma'ālim Al-Tanzῑl, which was discovered in the 19th century. This commentary book uses an Arabic introduction and was written outside the archipelago. And finally Kiai Sholeh Darat with his interpretation Tafsir Faidh Al-Rahmān which was detected at the end of the 19th century. This book uses Javanese (Pegon Arabic).